PENGGUNAAN SANTAN KELAPA DAN WHIPPING CREAM DALAM PEMBUATAN ES KRIM BERBASIS TERUNG BELANDA DAN BIJI SAGA - Putri Junita; Rahmayuni; Emma Riftyan (SAGU, 2023)
Ice cream is a frozen food made from cow’s milk which is very popular with the public. This study aims to get the best formulation using coconut milk and whipping cream for the quality of Tamarillo ice cream which refers to SNI No. 01=3713-1995. This study used a completely randomized design with five treatments and four replications resulting in 20 experimental units. The treatment in this study was the comparison of coconut milk and whipping cream in making Tamarillo ice cream. The formulations used were SW1 (90:10), SW2 (80:20), SW3 (70:30), SW4 (60:40), SW5 (50:50). Parameters observed were fat content, protein content, overrun, total solids, melting time, and sensory assessment (descriptive and hedonic). The results showed that the ratio of coconut milk and whipping cream in Tamarillo ice cream had a significant effect on fat content, protein content, total solids, melting time, and sensory assessment. SW3 (70:30) was the best treatment with 4.09% fat content, 18.03% protein content, 35.26% total solids, 19.55% overrun, and 13.53 minutes melting time.